2013
DOI: 10.1073/pnas.1216209110
|View full text |Cite
|
Sign up to set email alerts
|

How vinculin regulates force transmission

Abstract: Focal adhesions mediate force transfer between ECM-integrin complexes and the cytoskeleton. Although vinculin has been implicated in force transmission, few direct measurements have been made, and there is little mechanistic insight. Using vinculinnull cells expressing vinculin mutants, we demonstrate that vinculin is not required for transmission of adhesive and traction forces but is necessary for myosin contractility-dependent adhesion strength and traction force and for the coupling of cell area and tracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
233
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(256 citation statements)
references
References 44 publications
20
233
3
Order By: Relevance
“…2, we observed a similar hierarchical organization of FA proteins along the z-dimension, with the N-C polarized orientation of talin that seems to span the FA core, linking with actin stress fibers. These results suggest that vinculin is dispensable for the stratified nanoscale architecture of FAs, consistent with previous studies documenting FA assembly and maturation in the absence of vinculin (33,34).…”
Section: Resultssupporting
confidence: 81%
“…2, we observed a similar hierarchical organization of FA proteins along the z-dimension, with the N-C polarized orientation of talin that seems to span the FA core, linking with actin stress fibers. These results suggest that vinculin is dispensable for the stratified nanoscale architecture of FAs, consistent with previous studies documenting FA assembly and maturation in the absence of vinculin (33,34).…”
Section: Resultssupporting
confidence: 81%
“…The interaction of vinculin with acidic phospholipids and ␣-actinin may also contribute to the conversion of vinculin to an open conformation (33)(34)(35). Mechanical forces exerted on cells may also promote stabilization of the activated open conformation of vinculin (36). Changes in the conformation of vinculin enable it to act as a molecular switch for connections between cytoskeletal actin filaments and membrane adhesion protein complexes during stimulation of the cell and thus regulate the transmission of mechanical forces between the cytoskeleton and the extracellular matrix during contraction, adhesion, and migration.…”
mentioning
confidence: 99%
“…To better understand the relative contribution of these two interfaces to FA force transfer as well as the force transfer pathway within FAs, we examined the traction force and adhesions strength of two vinculin mutants: (1) a molecule comprising only V H (1-851) and lacking most of the proline-rich strap and actinbinding tail, and (2) a full-length vinculin (T12) with mutations in several key residues responsible for the strong head-tail interaction, promoting an active confirmation of the protein capable of readily binding talin and actin. 3 We found that V H does not increase traction force whereas T12 increased traction force by 2-fold over vinculin-null cells and 40% over wild-type vinculin, suggesting that connectivity between extracellular matrixintegrin clusters and the actin CSK is required for the generation of strong traction forces. These vinculin-mediated increases in traction force could be mediated by direct and indirect interactions with the actin CSK.…”
Section: Vinculin Regulates But Is Not Required For the Generation mentioning
confidence: 84%
“…Indeed, the study of force-FA relationships is the central focus of our lab. [2][3][4][5][6] FAs regulate their size, shape, and molecular composition in response to a variety of mechanical stimuli, including substrate stiffness, externally applied forces, and internally generated contractile forces. 7,8 The molecular mechanisms that govern FA mechanoresponses remain, however, largely unknown.…”
Section: A Helping Handmentioning
confidence: 99%
See 1 more Smart Citation